Punitive governance and the criminalization of socioenvironmental, anti-austerity, and anticorruption mobilizations in Puerto Rico - Atiles-Osoria, José M. (Critical criminology, 2022)
This paper shows how the Puerto Rican government has used punitive governance to deal with three important reactions to the multilayered crisis affecting Puerto Rico since 2006: socioenvironmental mobilizations; anti-austerity mobilizations; and anticorruption mobilizations. The paper proposes a threefold analysis. Firstly, it provides a brief overview of the Puerto Rican economic and financial crisis, the neoliberal solutions to the crisis, and its consequences. Secondly, the paper expands on the intertwined / intertwining relationship between punitive governance, colonialism, and criminal law. Thirdly, the paper analyzes the process of criminalization of the socioenvironmental, anti-austerity, and anticorruption mobilizations resisting colonial abandonment. Two strategies will be discussed: (1) the uses of criminal law to limit freedom of speech and protests and (2) repression and the systemic deployment of state violence against protestors. The state’s violent reactions to sociopolitical mobilizations are part of a long history of criminalizing and repressive practices that must be understood against the backdrop of US colonial history in Puerto Rico.